2017
DOI: 10.1007/s12529-017-9646-3
|View full text |Cite
|
Sign up to set email alerts
|

Unique Contributions of Acceptance and Catastrophizing on Chronic Pain Adaptation

Abstract: Findings from the current study indicate a pattern of results similar to prior studies in which greater levels of catastrophic thinking is associated with higher perceived pain intensity whereas greater levels of acceptance relate to better functioning in activities despite chronic pain. However, in the current study, both acceptance and catastrophizing were associated with negative affect. These relationships were significant beyond the effects of clinical and demographic variables. These results support the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…Consistent with the robust literature on the intrapersonal effects of catastrophizing about one’s own pain (Buenaver et al , 2008; Craner et al , 2017; Durand et al , 2017; Fisher et al , 2017), greater parent and child catastrophizing about their own pain were associated with higher usual pain intensity over the previous 3 months. Higher child catastrophizing about their own pain was also associated with greater child anxiety during the CPT.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Consistent with the robust literature on the intrapersonal effects of catastrophizing about one’s own pain (Buenaver et al , 2008; Craner et al , 2017; Durand et al , 2017; Fisher et al , 2017), greater parent and child catastrophizing about their own pain were associated with higher usual pain intensity over the previous 3 months. Higher child catastrophizing about their own pain was also associated with greater child anxiety during the CPT.…”
Section: Discussionsupporting
confidence: 68%
“…Much research has examined the intra‐ and interpersonal influences of catastrophizing about one’s own pain. Robust evidence of the role of increased catastrophizing about one’s own pain in predicting one’s own poorer pain and mental health outcomes is found in adults and children with and without chronic pain (Birnie, Chambers, Chorney, Fernandez, & McGrath, 2016; Buenaver, Edwards, Smith, Gramling, & Haythornthwaite, 2008; Craner, Sperry, Koball, Morrison, & Gilliam, 2017; Fisher, Heathcote, Eccleston, Simons, & Palermo, 2017). Catastrophizing about one’s own pain predicts own pain‐related outcomes beyond the influence of similar constructs (e.g., neuroticism, negative affectivity, anxiety; Goubert, Crombez, & Van Damme, 2004; Tran et al , 2015; Vervoort, Goubert, Eccleston, Bijttebier, & Crombez, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews have concluded that greater self-efficacy beliefs, including pain self-efficacy, are associated with and predict less pain intensity and disability in people with chronic pain [ 20 , 22 ]. Observational studies have found that greater pain acceptance is linked to less chronic pain intensity and pain interference in addition to better performance of daily activities [ 58 , 59 ]. Preliminary research has also found that trait optimism is associated with lower levels of pain intensity and disability in individuals with chronic pain [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain acceptance is a moment-to-moment process in which the individual has a willingness to actively experience pain along with related thoughts, feelings, and actions while acting in line with their values and goals [10]. Pain acceptance is an essential contributor to the outcomes of many types of chronic pain [11]. According to McCracken et al., pain acceptance is comprised of two core elements: pain willingness (PW) and activity engagement (AE).…”
Section: Introductionmentioning
confidence: 99%